Antibiotic sensitivity test of Escherichia coli and Staphylococcus aureus isolated from the reproductive tract of dairy cows - Baswendra Triadi; Suwarno Suwarno; Suryanie Sarudji; Ratna Damayanti; Rahmi Sugihartuti; Agnes Theresia Soelih Estoepangesti (Ovozoa: Journal of Animal Reproduction, 2022)
The purpose of this study was to determine the sensitivity of Staphylococcus aureus and Escherichia coli isolated from the reproductive tract of dairy cows during estrus to tetracycline, gentamicin, amoxicillin, and ciprofloxacin. Isolation and identification of E. coli and S. aureus from 24 cervical mucus samples resulted 15 samples containing E. coli and one sample containing S. aureus. Sensitivity test was performed using Kirby-Bauer (disc diffusion) method and interpreted using the Clinical and Laboratory Standards Institute (CLSI, 2017) guidelines. The sensitivity test of 15 isolates of E. coli showed 100% sensitivity to ciprofloxacin and tetracycline. For gentamicin, 14 (93.3%) isolates were sensitive, and 1 (6.7%) isolate was resistant, while for amoxicillin, 14 (93.3%) isolates were sensitive, and 1 (6.7%) isolate were intermediate. The sensitivity test of one isolate of S. aureus showed 100% sensitivity to ciprofloxacin, gentamicin, and amoxicillin; as for tetracycline 100% isolates were declared resistant.